DC Bias Risk Assessment of Power Grid Based on Extreme Value Estimation. (February 2019) - Weili, WU; Lin, Jiang
Abstract: The HVDC single-pole operation mode gives the Hami grid be in the risk of DC bias. Grasp the DC bias level of AC power in extreme cases can provide a basis for the defense system failure risk. In this paper, the DC bias risk assessment method of Hami power grid based on extreme value theory is put forward. Firstly, the method of continental plate and soil is analyzed. Secondly, the DC bias risk evaluation index for the power grid is constructed. Finally, the risk level of DC bias of Hami power grid is assessed. The results can provide a theoretical reference for defusing the DC bias risk caused by DC transmission.